The Mughal Dynasty in India: Genealogy of Power, Expansionist Politics, and the Causes of Its Decline (1526–1858): Dinasti Mughol India: Genealogi Kekuasaan, Politik Ekspansi dan Sebab-Sebab Kemundurannya (1526–1858) - Ajmain , Maftuh (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2026)
The Mughal Dynasty in India was one of the largest political powers in the history of the Islamic world, ruling from 1526 to 1858. This article examines the origins of this dynasty, the development of its administration from Babur to Aurangzeb, as well as the various political, economic, artistic, and cultural advancements achieved. Furthermore, this study analyzes the internal and external factors that led to its decline and eventual collapse in the mid-19th century. Using a historical-descriptive approach, this research demonstrates that the initial success of the Mughal Dynasty was underpinned by strong leadership, measured expansion, and a culture of tolerance. Conversely, its decline was triggered by weakening leadership, internal conflicts, the resurgence of Hindu society, and British colonial intervention through the British East India Company. These findings emphasize that the dynamics of Mughal triumph and collapse serve as a significant example of the relationship between leadership, social stability, and foreign political influence in the history of Islam in South Asia. [Dinasti Mughol India merupakan salah satu kekuatan politik terbesar dalam sejarah dunia Islam yang berkuasa sejak tahun 1526 hingga 1858. Artikel ini mengkaji asal-usul kemunculan dinasti ini, perkembangan pemerintahan dari Babur hingga Aurangzeb, serta berbagai kemajuan politik, ekonomi, seni, dan budaya yang dicapai. Selain itu, tulisan ini juga menelaah faktor-faktor internal dan eksternal yang menyebabkan kemunduran dan kehancurannya pada pertengahan abad ke-19. Dengan pendekatan historis-deskriptif, penelitian ini menunjukkan bahwa keberhasilan awal dinasti Mughol ditopang oleh kepemimpinan kuat, ekspansi terukur, dan budaya toleransi, sedangkan kemundurannya dipicu oleh melemahnya kepemimpinan, konflik internal, kebangkitan masyarakat Hindu, serta intervensi kolonial Inggris melalui British East India Company. Temuan ini menegaskan bahwa dinamika kejayaan dan keruntuhan Mughol merupakan contoh penting hubungan antara kepemimpinan, stabilitas sosial, dan kekuatan politik asing dalam sejarah Islam di Asia Selatan.]